The Legal Nature of The Doctor’s Civil Responsibility - مخلوف هشام (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2021)
This study examines the foundations of considering a doctor civilly responsible, so the medical activities practiced by the doctor that the patient’s body may cause errors or damages due to civil accountability, so the study comes to show the legal nature of this civil responsibility, because there are those who considerate a tort or contractual responsibility, and there are who go to say that it is based on considerations of tolerance of emerging consequences or security, and even the theory of commitment to safety, according to the different legal foundations of the matter, the civil liability of the doctor differs.